Mu'awiyah: Penggagas Pertama Sistem Monarki dalam Islam - Nurhasan, Nurhasan (Buletin Al-Turas, 2011)
The controversy of who proposed the first idea of monarcy in Islam is resolved. Classical sources mentioned that the first initiator was Mughirah ibn Shu'bah, but is was refuted because it was not rational and anachronic (not in order of time). Other sources mention Mu'awiyah was the first to initiate the idea of monarcy in Islam. He was the caliph who nwas able to organize traditional authory of arabic tribes (the authority of a tribal shaykh) into a kind of kingdom. THe first thing he did was to create the caliphate system that has been running since the days of caliphate (Khulafa Rasidun) as caliphate plus kingdom (khilafat al-mulk). This makes the leader not only as calliph but also as king. As the Caliph, Mu'awiyah cannot actually be called as "king", but more to the most prominent Arab lelader (as primus inter pares). However, Mu'awiyah managed to build a new government system in Islam, namely monarchy.